Respon Pertumbuhan Dan Hasil Dua Varietas Tomat Terhadap Pemberian Pupuk Organik Cair Super ACI - Ellok Dwi Sulichantini (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The objectives of the research were: (1) to determine growth and yield response of two tomato varieties upon the application of POC super ACI, and (2) to obtain suitable concentrations of POC super ACI for tomato crop.This research was polybag trials using completely randomized design (CRD) with factorial analysis and 5 replications.  The first factor was the variety, consists of two levels: Ranti and Ratna.  The second factor was the concentration of liquid organic fertilizer, consists of 4 levels, namely 0.00; 0.75; 1.50; and 2.25 ml/l.  Data were analyzed using analysis of variance and if there was a significant difference, then the test used Least Significant Difference (LSD) at 5%.The results revealed that: (1) Treatment of varieties affected significantly on the plant height increment at age of 15, 30, 45, and 60 days after planting and harvesting; days to flowering; number of fruit per crop and fruit fresh weight. Ratna variety produce fruit weight of 239.63 g/polybag while Ranti was 79.08 g/polybag;  (2) The concentration of POC Super ACI affected significanlty on the plant height increment at age of 15, 30, 45, and 60 days after planting and harvesting; number of fruit per crop and fruit fresh weight.  The best fertilizer concentration was 1.50 ml/l water that can produce fruit fresh weight of 194.68 g; and (3) The interaction between varieties and fertilizer concentrations did not affect significantly on all variables observed.